Multimodal virtual environments: an opportunity to improve fire safety training?. Issue 2 (2nd July 2020) - Lawson, Glyn; Roper, T.; Shaw, E.; Hsieh, M. K.; Cobb, S. V.
Abstract: Fires and fire-related fatalities remain a tragic and frequent occurrence. Evidence has shown that humans adopt sub-optimal behaviours during fire incidents and, therefore, training is one possible means to improve occupant survival rates. We present the potential benefits of using Virtual Environment Training (VET) for fire evacuation. These include experiential and active learning, the ability to interact with contexts which would be dangerous to experience in real life, the ability to customise training and scenarios to the learner, and analytics on learner performance. While several studies have investigated fire safety in VET, generally with positive outcomes, challenges related to cybersickness, interaction and content creation remain. Moreover, issues such as lack of behavioural realism have been attributed to the lack realistic sensory feedback. We argue for multimodal (visual, audio, olfactory, heat) virtual fire safety training to address limitations with existing simulators, and ultimately improve the outcomes of fire incidents.